Simulación de circuitos de iluminación comercial - Maza Pinos, Edwin Fernando (2015)
This present thesis job of Industrial Control Electrician Technology Career that follows as an fundamental goal is the utilization of the modern tool for simulation projects lighting in locals commercials so that constitutes in a bibliography document of researching for professional in formation.in the career after mentioned. The Lighting Project in local commercials is not an easy task so that is after doing it any lighting interference. We have to take into account the kind of establishment the good or service that offers the local dimension, Its location and above all that message that you want to transmit to the costumers This document is describing in a set way, the theoretical foundations of commercial spaces, the main lighting concepts, and the modern equipment lighting. It’s shows as main results the methodology of DIALUX software management through two practices are using lights of different trademarks.